bahasa inggria: (Analysis of Q.S Al-Ikhlas) - al Jufri, Ali; Lute, Wardi; Rafiiy, Muhammad; Syamsuri, Syamsuri (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
This study examines the practice of the tradition of throwing stones at funeral ceremonies in Landonan Bebeau Village, Central Sulawesi Province, Indonesia. This practice is carried out collectively, namely through gatherings, at certain times and places. To see how the people of Landonan Bebeau Village are involved in communicating with the Qur'an, this Living Qur'an study focuses on two important things: the practice of Surah Al-Ikhlas and the tradition of throwing stones at funeral ceremonies in Landonan Bebeau Village, as well as the nature of the tradition of throwing stones at the ceremony. This study is a field research, using a phenomenological and sociological approach, and using Living Qur'an analysis. The results of this study conclude that the practice of the tradition of throwing stones by reciting Surah Al-Ikhlas 3,333 times is intended to reward or pray for the deceased to receive rewards and be given relief from the punishment of the grave, and to foster friendship between residents. The authors discovered the rationale behind the use of Surah Al-Ikhlas in the stone-throwing tradition. It is the shortest surah in the Quran and holds significant virtues, including freedom from the torment of the grave. The authors suspect that this motivation underlies the stone-throwing tradition. الملخص تتناول هذه المقالة ممارسة الرجم في مراسم الجنازة بقرية لاندونان بيبو، مقاطعة سولاويزي الوسطى، إندونيسيا. تُمارس هذه الممارسة جماعيًا، من خلال تجمعات، في أوقات وأماكن محددة. ولدراسة مدى مشاركة مجتمع لاندونان بيبو في التواصل مع القرآن الكريم، تُركز هذه الدراسة، التي تُعنى بالقرآن الحي، على جانبين رئيسيين: قراءة سورة الإخلاص، وتقليد الرجم في مراسم الجنازة بقرية لاندونان بيبو، بالإضافة إلى جوهر هذه العادة. تُعدّ هذه الدراسة بحثًا ميدانيًا، يعتمد على مناهج ظاهرية واجتماعية، وتحليلات القرآن الحي. وتخلص النتائج إلى أن ممارسة الرجم، بتلاوة سورة الإخلاص 3333 مرة، تهدف إلى مكافأة الميت أو الدعاء له بالثواب والنجاة من عذاب القبر، وتعزيز صلة الرحم بين السكان. اكتشف المؤلف السبب وراء استخدام سورة الإخلاص في تقليد رمي الجمرات. فهي أقصر سورة في القرآن الكريم، ولها فضائل جليلة، منها النجاة من عذاب القبر. ويظن المؤلف أن هذا الدافع هو أساس تقليد رمي الجمرات. Abstrak Penelitian ini mengkaji tentang praktik pelaksanaan tradisi buang batu pada upacara kematian di Desa Landonan Bebeau Provinsi Sulawesi Tengah Indonesia. Praktik ini dilakukan secara bersama-sama yakni melalui perkumpulan, waktu dan tempat tertentu. Untuk melihat bagaimana keterlibatan masyarakat Desa Landonan Bebeau dalam berkomunikasi dengan Al-Qur’an, maka kajian Living Qur’an ini difokuskan pada dua hal penting yaitu pengamalan surah Al- Ikhlas dan tradisi buang batu pada upacara kematian di Desa Landonan Bebeau serta hakikat kegiatan tradisi lempar batu pada upacara tersebut. Penelitian ini merupakan penelitian lapangan (field research), dengan menggunakan pendekatan fenomenologi dan sosiologi, dan menggunakan analisis Living Qur’an. Hasil penelitian ini menyimpulkan bahwa dengan adanya praktik pelaksanaan tradisi buang batu dengan membacakan surah Al-Ikhlas sebanyak 3.333 kali dimaksudkan untuk menghadiahkan atau mendoakan si jenazah agar mendapat pahala dan diberi keringanan dari siksa kubur, dan guna menjalin silaturahmi antar warga. Penulis menemukan alasan di balik penggunaan surah Al-ikhlas dalam prosesi tradisi buang batu, yakni surah Al-Ikhlas merupakan surah terpendek yang ada di dalam Al-Qur’an dan memiliki fadhilah yang besar salah satunya adalah dibebaskan dari siksa kubur. Penulis menduga bahwa motivasi itulah yang menjadi dasar pelaksanaan tradisi buang batu.